Sero-epidemiological investigation and cross-neutralization activity against SARS-CoV-2 variants in cats and dogs, Thailand - Suwanpakdee, Sarin; Ketchim, Natthaphat; Thongdee, Metawee; Chaiwattanarungruengpaisan, Somjit; Tangsudjai, Siriporn; Wiriyarat, Witthawat; Julapanthong, Pruksa; Trakoolchaisri, Wachira; Buamas, Supakit; Sakcamduang, Walasinee; Okada, Pilailuk Akkapaiboon; Puthavathana, Pilaipan; et al. (Frontiers in Veterinary Science, 2024)
Epidemiological data on SARS-CoV-2 infection in companion animals has been thoroughly investigated in many countries. However, the information on the neutralizing cross-reactivity against SARS-CoV-2 variants in companion animals is still limited. Here, we explored the neutralizing antibodies against SARS-CoV-2 in cats and dogs between May 2020 and December 2021 during the first wave (a Wuhan-Hu-1-dominant period) and the fourth waves (a Delta-dominant period) of the Thailand COVID-19 outbreak. Archival plasma samples of 1304 cats and 1795 dogs (total = 3099) submitted for diagnosis and health check were collected at the